2020
DOI: 10.1002/oby.23045
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Eating Predicts Weight Regain Among Black Women in the SisterTalk Intervention

Abstract: Objective This study aimed to assess effects of emotional eating and stress on weight change among Black women in a culturally tailored weight‐control program. Methods SisterTalk, a cable‐TV‐delivered weight‐control randomized trial, included 331 Black women (aged 18‐75 years; BMI ≥ 25 kg/m2) in Boston, Massachusetts. BMI and waist circumference (WC) were assessed at baseline and 3, 8, and 12 months post randomization. Frequency of “eating when depressed or sad” (EWD) and “eating to manage stress” (ETMS) (i.e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…More than half of the adults with obesity have been found to display characteristics of emotional eating (Péneau et al., 2013; Wong et al., 2020), increasing one's tendency to display dysfunctional eating behaviours such as binge‐eating and disinhibited/unrestrained eating (Escandón‐Nagel et al., 2018; Wiedemann et al., 2018). Such eating behaviours have in turn been associated with depression, weight gain, weight‐loss failure and weight regain (Braden et al., 2016; Risica et al., 2021). While there is no specific definition for what constitutes an ‘emotional eating intervention’, some weight‐loss interventions including physical activity, stress reduction, mindfulness‐based interventions (MBI), Acceptance and Commitment Therapy (ACT), Cognitive Behaviour Therapy (CBT) and Dialectical Behaviour Therapy (DBT; Lawlor et al., 2020; Frayn et al., 2018; Frayn & Knäuper, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…More than half of the adults with obesity have been found to display characteristics of emotional eating (Péneau et al., 2013; Wong et al., 2020), increasing one's tendency to display dysfunctional eating behaviours such as binge‐eating and disinhibited/unrestrained eating (Escandón‐Nagel et al., 2018; Wiedemann et al., 2018). Such eating behaviours have in turn been associated with depression, weight gain, weight‐loss failure and weight regain (Braden et al., 2016; Risica et al., 2021). While there is no specific definition for what constitutes an ‘emotional eating intervention’, some weight‐loss interventions including physical activity, stress reduction, mindfulness‐based interventions (MBI), Acceptance and Commitment Therapy (ACT), Cognitive Behaviour Therapy (CBT) and Dialectical Behaviour Therapy (DBT; Lawlor et al., 2020; Frayn et al., 2018; Frayn & Knäuper, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that negative emotions increase the risk of emotional eating behavior [12,13]. Emotional eating is defined as overeating after stress and negative emotions [14]. People tend to eat as a mechanism to cope with mood changes [15].…”
Section: Introductionmentioning
confidence: 99%
“…Emotional eating refers to the tendency to overeat in response to stress and negative emotions, such as anger, fear, boredom, sadness, and loneliness, as a means of coping with emotional fluctuations ( Risica et al, 2021 ). It is more prevalent among individuals who are overweight or obese ( Betancourt-Núñez et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%